Affective Commitment as a Mediator in the Relationship Between Motivation and Member Performance - Fauzi, Gerry Fernaldy; Astuty, Isthofaina (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze, identify, and explain the direct effect of motivation on affective commitment, the direct impact of affective commitment on member performance, the direct influence of motivation on member performance, and the indirect impact of motivation on member performance with affective commitment as a mediating variable. This research was conducted within the Youthpreneur community, with a sample of 125 respondents obtained through a questionnaire. The sampling technique used is the census sampling method, based on the criteria of at least one year of management, and the sample consists of members and administrators of the organization. The analytical method employed is regression analysis, processed through the Statistical Package for the Social Sciences (SPSS) version 22. The results of this study show that motivation has a significant positive effect on affective commitment, affective commitment has a significant positive effect on member performance, motivation does not have a positive and significant effect on member performance, and affective commitment can act as a mediating variable in the relationship between motivation and member performance.